Contribution to thermal study of modified cement pastes based on siliceous SCMs. (6th April 2019) - Arroudj, Karima; Oudjit, Mohamed Nadjib; Tagnit-Hamou, Arezki
This study aims to highlight siliceous additive available in Algeria: ground blast furnace slag 'S' and dune sand or Quartz 'Q' compared to silica fume 'SF'. Monitoring the hydration of cement pastes modified by replacing 15% additive by thermal analysis (Differential thermal and thermo gravimetric analysis -DTA/TG) quantifies the Portlandite consumed by the additive, the combined water 'Wn' and the degree of hydration as function of time. The results of this study confirm and complement those found in previous research: compared to SF and S, quartz has a low pozzolanic activity resulted in consumption of Portlandite released during cement hydration. This study is completed by mechanical tests on ultra high performance concrete (UHPC), with a same level of replacement. A new generation of sustainable and eco-concrete is obtained based on local materials.